Symposium 3: The Tyranny of Participation and Collaboration in Networked Learning - Ferreday, Debra; Hodgson, Vivien (Proceedings of the International Conference on Networked Learning, 2008)
It has increasingly become the case that the ideas underpinning the concept and theory of networked learning have moved on from the ’original’ definition to ones that assume a major benefit offered by NL from a learning perspective is the opportunities for collaboration and participation in the learning process. As it has evolved, networked learning has come to emphasise the importance of the collaborative learning aspects and possibilities of learning in online spaces (McConnell 2000, Steeples and Jones 2002). In particular, the concept of collaboration is almost universally assumed to be an unquestionably desirable aspect of this type of learning. In this paper, we suggest that such a utopian view of participation which does not acknowledge the ’dark side’ of participation in learning that else where in the literature authors such as Reynolds (1998) and Brookfield (1994), amongst others, have identified as an important issue. This paper therefore examines more closely some of the darker sides of participation. We suggest that the tendency to view collaboration as universally good can in some cases be experienced as normative. This, we argue, creates a form of tyranny in which participation, rather than achieving a liberating effect can become (albeit often with the best intentions) an instrument of domination which some learners may experience as oppressive and controlling. We argue this is most likely to be the case in the absence of reflexivity and understanding of different ways and approaches to participation. We go on to identify some of the forms this tyranny can take in practice; these include the operational constraints of the institutional context; the failure to recognise the impact of different, changing and multiple identities of individuals on their choices about how (and whether) to participate; and failure to reflect on the ways in which ideals of participation result in the adopting largely unrecognized practices of inclusion and exclusion. All these examples starkly illustrate how harmful a naïvely utopian model of participation can be in practice. They illustrate that participation and collaboration is no romantic ideal and what’s more has the potential to undermine learning if not considered from a less utopian perspective. In the paper we suggest an alternative and potentially more productive perspective is, after Foucault, a heterotopian one. A perspective that acknowledges and assumes disruption and which disturbs our customary notion of ourselves. Participation in heterotopian spaces is disturbing and ambiguous, but it offers a space in which to imagine, to act, and to desire differently. We try to illustrate through a particular example the potential that participative processes have to be experienced as tyrannical when participation is demanded in an unreflective and normative way. The example given demonstrates how a rigid invocation of community norms around the notion of support led to frustration and tension which resulted in not only the marginalisation of one individual but also experienced as a threat to the ideal of a learning community for a number of the participants. We suggest that rather than pursue participation in this both utopian and inflexible fashion that a less tyrannical alternative is to expect and anticipate that participation will be disruptive and encompass difference and variety. That is, in a way that reflects a heterotopian rather than utopian view of participation. A heterotopian view of participation acknowledges that it may well and often does test our customary notions of ourselves but at the same time in doing so offers the possibility of heterotopian spaces to imagine and desire differently, not in a utopian, normative or comfortable sense but in a heterotopian, often disturbing and disruptive sense.